Covid-19 and journalism conundrums: a study on dilemmas in content selection - Sushmita, Chelin Indra; Pawito, Pawito; Rahmanto, Andre Novie (Jurnal Studi Komunikasi, 2021)
The study examined journalism practices covering Coronavirus disease (Covid-19), particularly online journalism in Solo, one of the metropolitan cities in Central Java Province of Indonesia. Solo is the first city in Indonesia to declare an extraordinary event due to the Covid-19 pandemic after coronavirus-linked deaths were reported. The notion of a dilemmatic situation, mainly in content selection, is the central perspective in this research. This research referred to news value theory and agenda-setting that used a qualitative approach method. The data were obtained through interviews with 20 journalists of online media in Solo. We also included non-participatory observation in the Solopos.com newsroom. The study suggests that, to some extent, journalists face a dilemma in choosing content to present news that concerns the public interest during the Covid-19 pandemic. The dilemma included determining interesting issues, attracting the public interest, and becoming meaningful to the readers, but not to endanger the personal safety and maintain professional sustainability because there is no news worthy of a life.